The Effect of Morning Waking Habits on The Discipline of Elementary School Students - Marpian, Marpian; Somantri, Mubarok; Supriatna, Encep; Fitriani, Yulianti; Marselina, Lind (International Conference on Elementary Education, 2025)
Character education is a crucial foundation for building a well-rounded generation, encompassing responsibility, consistency, and order alongside discipline. These attributes are vital for future-ready learners, aligning directly with the Sustainable Development Goals (SDGs) for Quality Education. This study addresses the issue of indiscipline in elementary schools by examining its link to morning waking habits, framed within the principles of Self-Regulation Theory. The main objective was to investigate the influence of morning waking habits on the discipline level of 5th-grade students at SDN Batucina and highlight its academic contribution. A quantitative descriptive correlational design was used with a total sample of 30 fifth-grade students. Data were collected using a Likert scale questionnaire. The findings indicate a very strong and positive correlation was found between morning waking habits and student discipline (r=0.752; p=0.000), with an effect size of 56.5%. In conclusion, the habit of waking up early is an effective strategy to develop self-regulation skills in young students, fostering consistency and responsibility that directly enhance their discipline. This finding provides crucial implications for designing sustainable character programs and 21st-century education by prioritizing consistent positive habits